Comparison of the real estate registration system of Montenegro and Ukraine - Hordieiev, A.; Tsibenko, B. (Land Management, Cadastre and Land Monitoring, 2026)
This study provides a comprehensive comparative analysis of the state registration systems for real property rights in Ukraine and Montenegro, considering contemporary challenges, trends in decentralization, and digitalization of cadastral and registration processes. The aim of the study was to identify similarities and differences in the legal foundations, organizational structure, and practical functioning of the registration systems in both countries, as well as to evaluate their effectiveness. The research employed general scientific and specialized methods: analysis and synthesis to summarize legislative norms, comparative legal method to identify differences between the Ukrainian and Montenegrin models, systems approach to assess the interaction of cadastral and registration authorities, and structural-functional method to reveal features of the organization of the state land cadastre and the property registry in Montenegro. Content analysis of specialized scientific publications was used, including work dedicated to the maintenance of state surveying in Montenegro. A historical and contemporary analysis of the registration systems in both countries was conducted. The study analyzed the stages of state registration formation, including inventory data, technical inventory bureaus, and modern bodies such as the Ministry of Justice and the State Geocadastre. It identified specifics of maintaining separate registries for land plots, houses, buildings, apartments, unfinished construction objects, and their encumbrances. The development of the Montenegrin system was reviewed, starting from the 1980s, including the transformation of the land cadastre into a unified real estate registration system through the Real Estate Administration. The study highlighted the constitutive nature of property registration, integration of cadastral and registration data, public access via electronic services such as eKatastar and Geoportal, as well as specifics of land geoclassification and legalization of unauthorized construction. Key characteristics of both countries’ systems were compared in tables, reflecting: legal basis of registration, organizational structure, objects and mechanisms of registry maintenance, digitalization, publicity, protection of property rights, and procedures for legalizing unauthorized buildings. The novelty of this study lies in the comprehensive comparison of the two systems in terms of legal effectiveness, digitalization, and protection of property rights. The conclusions of the research can be used to improve the Ukrainian real estate registration model, integrate cadastral and registration processes, and enhance legal certainty, bringing it closer to European standards. Received: 10.12.2025; Accepted:15.01.2026;